Self expressions : mind, morals, and the meaning of life - Flanagan, Owen, Jr., 1949- (Philosophy of mind series., 1996)
What makes the life of any animal, even one as sophisticated as Homo sapiens, worth anything? What place in a material world is there for God? And if there is no place for a God, then what hold can morality possibly have on us? Why isn't everything allowed? In this trailblazing collection of essays on free will and the human mind, distinguished philosopher Owen Flanagan tackles these questions and more. He pursues the old philosophical project of reconciling a scientific view of ourselves with a view of ourselves as agents of free will and meaning-makers. But he approaches this project from new angles, bringing in the latest insights of neuroscience, cognitive science, and psychiatry.